A relação entre o comitê de auditoria e a opinião do auditor independente - Silva, Jorge Luiz Rosa da (Universidade do Vale do Rio dos Sinos, 2023)
This thesis aimed to verify whether the activities of the audit committee impact the opinion of independent auditors. The research was based on Agency Theory, based on the assumptions of information asymmetry, agency conflicts and agency costs. For that, a questionnaire with open questions was elaborated, which was answered by ten members of the audit committees, from public and private companies and by six independent auditors, in the State of Rio Grande do Sul. For data processing, Laurence Bardin's Content Analysis technique was used. The results suggest that, from the respondents' perception, the activities of the audit committees, carried out in full or in part, summarized using the committees' reports, impact the opinion of the independent auditors. It was confirmed that the use of these reports by the auditor or any other information does not compromise its independence. Confirmation was obtained of the use of the committees' reports, by the independent auditor, as evidence to complement their work. Auditors and members of audit committees confirmed, for the most part, that the opinion of independent auditors is impacted by the use of audit committee reports. The results contribute to strengthening the activities of the audit committees, which consequently will end up making the organizations' corporate governance more robust.
Keywords: Comitê de auditoria; Auditor independente; Opinião do auditor; Relatório do comitê de auditoria; Audit committee; Independent auditor; Auditor's opinion; Audit committee report; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis